Brooke's quest for captain - Jones, Jen (Jones, Jen. Team cheer, 2012)
Brooke Perrino really wants to be captain of her school cheerleading team, but she is having trouble with eighth-grade algebra and suddenly she is beginning to doubt her ability to handle the pressure.